2020
DOI: 10.1088/1361-6587/ab97f3
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating laser-driven proton acceleration with tailored target density profile

Abstract: Two-dimensional particle-in-cell simulations show that when an intense picosecond laser pulse irradiates a target with steep but smooth density profile, the target protons can be accelerated to high energies with small divergence by a combination of target normal sheath acceleration and radiation pressure acceleration. The effects of plasma density profile on proton acceleration and collimation are investigated. In general, smaller(larger) density gradients lead to larger(smaller) self-generated azimuthal magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…, where j = e, p, C. Unless stated otherwise, the initial peak electron density is n e0 ∼ 15n cr , i.e., in the density regime of 10 22 cm −3 , where n cr = m e ω 2 /4πe 2 is the critical density, − e the electron charge, m e the electron mass, and ω the laser frequency. Such density distributions can be obtained by nanosecond laser ablation [25]. We shall consider carbon-to-proton density ratios R = n C0 /n p0 = 9, 1, 1/9 (cases 1 to 3, respectively), corresponding to n C0 /n cr = 2.5, 2.2, 1 and n p0 /n cr = 0.28, 2.2, 9, respectively, representing high to low carbon content of the target.…”
Section: Simulation Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…, where j = e, p, C. Unless stated otherwise, the initial peak electron density is n e0 ∼ 15n cr , i.e., in the density regime of 10 22 cm −3 , where n cr = m e ω 2 /4πe 2 is the critical density, − e the electron charge, m e the electron mass, and ω the laser frequency. Such density distributions can be obtained by nanosecond laser ablation [25]. We shall consider carbon-to-proton density ratios R = n C0 /n p0 = 9, 1, 1/9 (cases 1 to 3, respectively), corresponding to n C0 /n cr = 2.5, 2.2, 1 and n p0 /n cr = 0.28, 2.2, 9, respectively, representing high to low carbon content of the target.…”
Section: Simulation Parametersmentioning
confidence: 99%
“…In RPA, the radiation pressure of an intense laser pushes forward the affected electrons of a dense target, producing a local charge-separation field that drives forward the target ions. Under suitable conditions, in RPA very energetic fast electrons can also propagate through the target and form behind it a chargeseparation field for TNSA of the backside ions [19][20][21][22][23][24][25][26][27][28]. That is, ions can be multiply accelerated by the dual-peaked charge-separation field: RPA at the target front and TNSA at the target back.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Svedung Wettervik, DuBois & Fülöp (2016) have shown using Eulerian Vlasov-Maxwell simulations that the final monoenergetic behaviour of the ions can be preserved with a target having a layered density structure. In a recent paper by Yang et al (2020), it was found that the interaction of intense lasers with modified targets having soliton-like density profiles can be administered to obtain energetic protons of controllable beam properties. It was observed that a steep density gradient resulted in protons accelerating with higher energies via an interplay of RPA and TNSA mechanisms with a higher angle of divergence.…”
Section: Introductionmentioning
confidence: 99%